PERAN EKONOMI SYARIAH DALAM MENDUKUNG TERWUJUDNYA SUSTAINABLE DEVELOPMENT GOALS (SDGs) DI INDONESIA - Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
Sharia Economics has a role in supporting the implementation of the SDGs in Indonesia with all existing product ecosystems. Starting with financial products, various halal food and beverages, Islamic entrepreneurs and others. The SDGs have 17 goals, including, without poverty, without hunger, a healthy and prosperous life, quality education, gender equality, clean water and proper sanitation, energy clean and affordable, decent work and economic growth, industry, innovation and infrastructure, reducing inequality, sustainable cities and communities, responsible consumption and production, tackling climate change, marine ecosystems, terrestrial ecosystems, peace, justice and resilient institutions, and partnership to achieve goals. The role of Islamic economics in the SDGs in Indonesia is that the characteristics that exist in Islamic finance are suitable for achieving the SDGs, such as social funds and their nature that is free from speculation. In addition, the existing contracts in Islamic finance, especially in the agricultural sector such as Mudharabah, Musyarakah, Muzara'ah, Musaqah, Murabahah, Ba'i Salam and sharia-based businesses with halal food and beverage products as well as Islamic entrepreneurs with various Sharia contracts such as Salam and Ijarah in Franchise, Musyarakah, Muzara'ah, Musaqah, Murabahah in livestock and agriculture are very supportive of the SDGs.